Foreign aid and revenue response: An examination of joint General Budget Support - Martin Knoll (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
The present paper explores the extent to which new joint General Budget Support (GBS) systems have been able to overcome the problems of aid dependency and negative fiscal incentives that can potentially result from high levels of on-budget aid. As approximately 90 percent of new joint GBS goes to sub-Saharan Africa, this analysis, which covers the period from 2000 to 2008, evaluates data from 37 sub-Saharan developing countries. According to fixed effect and system GMM estimations, joint GBS assistance - although highly discretionary - does not undermine recipients' revenue mobilization efforts. Indeed, on the contrary, while aid in general has no measurable impact on recipients' revenue performance, joint GBS programs are associated with higher revenue mobilization. This suggests that on-budget aid delivered under well-targeted conditionality successfully mitigates adverse fiscal incentives while substantially enhancing recipients' fiscal space.
Keywords: C33; F35; O23; O55; 330; budget support; fiscal response; revenue mobilization; sub-Saharan Africa